An Experimental Study of Greenhouse Gas Concentration on the Maximum Power Point of Solar PV Panels - Patnaik, B.; Swain, S. C.; Rout, U. K. (Engineering, Technology & Applied Science Research, 2020)
The energy demand increases along with demographic and development growth. India is the second-most populous country in the world and most of its population needs more energy as its human and energy development indices are rather low. So, the country depends on cheaper sources of energy which have ample effects on the environment. Many energy sources are polluting, but solar energy is pollution-free and its availability is abundant with zero cost. Solar Photo Voltaic (PV) technology is the best technology to harness electricity. The effect of varying environmental factors regulates the performance factors of this technology. Its efficiency mainly depends on the concentration of greenhouse gases (GHGs), ambient temperature, module temperature, incoming solar radiation intensity, and PV material composition. To understand the behavior of solar panels on maximum power point under various GHGs concentrations, three experiments were conducted. One in normal atmospheric CO2 concentration and two in higher CO2 concentration chambers.